Desafios para a implementação do Programa PRONATEC/Osasco sem miséria: proposta de Plano de Ação para a Secretaria Municipal de Desenvolvimento: trabalho e inclusão - Trogiani, Caio de Resende (2012)
The aim of this study was to identify the reasons behind the high student dropout rates and low enrollment index of the Access to Technical Learning and to Jobs National Program (PRONATEC) under the scope of Brazil without Extreme Poverty Plan (Brasil Sem Miséria) in the city of Osasco. For this purpose, a quantitative research was done through a survey applied to participants of the pre-enrollment event; and qualitative research based on semi-structured interviews and focus groups with municipal managers working within the Program, managers and educators of the institutions which offer the courses, regular students, dropout students and people who were invited to attend the courses but did not respond to the invitation. Altogether, 122 people participated in the qualitative research. Thereby, a list of 27 problems was identified and divided into five groups: Policy Conception, Target Public Characteristics, Program’s Disclosure, Program´s Operation and Courses Offering. Based on the prioritization of these problems, an Action Plan was proposed to the Secretary of Development, Labor and Inclusion, which is responsible for the implementation of PRONATEC in Osasco.